2019
DOI: 10.5455/aim.2019.27.162-166
|View full text |Cite
|
Sign up to set email alerts
|

Noise Effect on Blood Pressure and Heart Rate - Regression Analysis in Service of Prediction

Abstract: Introduction: Investigations have shown that noise is one of the etiologic factors that leads to a risk of cardiovascular incidence. Aim: To present effect of noise on arterial tension and heart rate of workers who work on machine press during period of three-years. Methods: The study had a prospective character and included 30 subjects (n = 30) who were monitored over a three-year period (36 months). The respondents worked at the factory "Cimos" on machine press (Zenica, Bosnia and Herzegovina). Ten machine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A total of 43 studies were identified that reported on the impact of noise exposure on heart rate [Table S11][ 29 30 31 44 48 50 52 57 59 62 67 69 70 74 75 76 77 79 80 82 86 87 92 99 101 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 ]; however, some of them could not be pooled into the meta-analysis due to differences in population, measurement of exposures, measurement of outcomes, and reporting of outcomes. [ 31 50 67 69 70 74 86 99 140 141 142 145 146 147 149 151 152 153 154 ] Concerns with the risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Tables S12 and S13]. As shown in Table 4 , there was very low CoE for the effects of increased noise exposure on heart rate.…”
Section: R Esultsmentioning
confidence: 99%
“…A total of 43 studies were identified that reported on the impact of noise exposure on heart rate [Table S11][ 29 30 31 44 48 50 52 57 59 62 67 69 70 74 75 76 77 79 80 82 86 87 92 99 101 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 ]; however, some of them could not be pooled into the meta-analysis due to differences in population, measurement of exposures, measurement of outcomes, and reporting of outcomes. [ 31 50 67 69 70 74 86 99 140 141 142 145 146 147 149 151 152 153 154 ] Concerns with the risk of bias due to confounding, exposure assessment, missing data, and measurement of outcomes were identified [Tables S12 and S13]. As shown in Table 4 , there was very low CoE for the effects of increased noise exposure on heart rate.…”
Section: R Esultsmentioning
confidence: 99%
“…In particular, numerous accounts of problematic noise levels and/or stressful auditory surroundings at hospitals have been published, expounding the harmful consequences to patient well-being during hospitalisation [47,[53][54][55][56][57]. These include, among others, poor sleep [58], increased blood pressure [59], impaired wound healing [60], and general discomfort and annoyance [55,61]. It is thus of great interest to pursue creating satisfactory auditory environments for meal-based activities in hospitals that ensure favourable bases for nutritional care and patient wellbeing.…”
Section: Acoustic Meal Environmentsmentioning
confidence: 99%
“…13 Veljovic et al stated that it is possible to predict body blood pressure for a period when exposed to a certain level of noise. 14…”
Section: Introductionmentioning
confidence: 99%
“…13 Veljovic et al stated that it is possible to predict body blood pressure for a period when exposed to a certain level of noise. 14 Despite the focus on exposure limits for noise to prevent hearing loss, there is restricted information about noise exposure limits to prevent non-auditory effects. Epidemiological studies have also not presented an accurate pattern between occupational noise exposure and non-auditory responses.…”
Section: Introductionmentioning
confidence: 99%